2020
DOI: 10.12776/qip.v24i2.1438
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Courier Service Quality in e-Commerce from Customers’ Perspective

Abstract: <p><strong>Purpose:</strong> In recent years, the increasing popularity of e-commerce has become a driving force behind the development of courier service both in Poland and worldwide. In order to face growing competition on courier market and meet clients’ expectations, one of the crucial strategic goal of courier operators is to provide high quality service. The aim of the article is to identify and classify the key factors which determine the perception of courier service quality by custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
2
30
1
1
Order By: Relevance
“…Even though the courier service is the last and crucial link in online shopping, studies concerning the relationship between trust and service quality are limited. Most research on the courier service was focused on measuring the service quality or customer satisfaction using the SERVQUAL method slightly modified according to the specificity of the express/courier branch [42]. However, only some of them indicated trust as the factor of service quality.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the courier service is the last and crucial link in online shopping, studies concerning the relationship between trust and service quality are limited. Most research on the courier service was focused on measuring the service quality or customer satisfaction using the SERVQUAL method slightly modified according to the specificity of the express/courier branch [42]. However, only some of them indicated trust as the factor of service quality.…”
Section: Introductionmentioning
confidence: 99%
“…A part of the obtained results was consistent with conclusions reached by other authors. Most previous studies also indicated the timeliness of delivery (TIM) as a priority dimension for customers using courier services [ 32 , 34 , 38 41 ]. Liu and Liu included the compliance and completeness of the order (COMP) among the most important factors determining the courier service quality analysed in this study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the scientific research conducted so far was mainly concentrated on identifying criteria/ attributes/factors affecting the courier service quality and the methods of evaluating them, omitting the existing relationship between the factors. The research on the courier service quality considered only one perspective, usually clients of courier services (individuals or business customers) [31][32][33][34][35][39][40][41][42] omitting the perspective of the sender-an online shop and a courier company. Considering the conclusions of analysed research on service quality, the article aims to analyse courier service quality from a multi-shareholder perspective, as it allows to formulate comprehensive and novel conclusions towards future directions of service quality.…”
Section: Literature Review Concerning the Courier Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…To conduct this research an online survey was conducted where there was a total of 120 participants the assessment was done based on respondents preferred courier services, frequency of delivery on different age group.it also evaluated the number of times users used the courier services before and during pandemic and preferred payment options. In [2] the author wants to identify and classify the key factors which determine the perception of courier service quality by customer shopping online, growing competition on courier market and meet client's expectations, one of the goals of courier services is to provide high quality service though there were some limitations to this research, the study was aiming to develop scale of courier service quality to verify the scale in future the author will use CFA In [3] the author wants to highlight and improve upon the existing courier system. This way they system provides the service which is less efficient in terms of comfort, cost estimation from consumers' point of view, tracking dispatch and cost estimation.…”
Section: Literature Reviewmentioning
confidence: 99%